Sams teach yourself responsive web design in 24 hours - Kyrnin, Jennifer (Sams teach yourself in 24 hours series., 2015)
"Sams Teach Yourself Responsive Web Design in 24 Hours helps you create websites that work equally well on everything from smartphones and tablets to multi-screen monitors. This book's straightforward, step-by-step approach shows how to use HTML, CSS, and JavaScript to build the responsive sites today's users and clients want. In just a few hours, you'll be building layouts, sites, forms, and web apps that automatically adapt to virtually any device. Every lesson builds on what you've already learned, giving you a rock-solid foundation for real-world success" -- Amazon.com.